TOLERANCE AND CARING: STRENGTHENING STUDENTS’ SOCIAL CHARACTER TO REALIZE SOCIETY 5.0 - Adison Adrianus Sihombing (Journal of Human Development and Communication (JoHDeC), 2025)
The transformation towards society 5.0 is often characterized by people’s behavior in digital public spaces causing widespread public unrest. This qualitative study aims to highlight, explore, and analyze the social character of people on social media who are less tolerant and caring. This study relies on secondary data from literature studies and online news. The finding is that there is a phenomenon of weakness in the social character of individuals and communities who tend to be intolerant and uncaring in digital public spaces. The habit of posting content or creating statuses that are abusive, threatening, intimidating, and behavior that spreads hoax news, hate speech, and flexing. Weak social character has implications for people’s habits of spreading news too quickly without caring about other people. Apart from that, the digital technology revolution brings a sense of comfort and entertainment, and anyone can express themselves on social media. Unfortunately, technological progress is not accompanied by the development of critical-analytical thinking skills. As a result, individual society behavior is too responsive-reactive in the digital space without thinking about the further impacts that might arise. This has had negative implications for social cohesion and relations and even legal issues. This study recommends strengthening social character with strategies for strengthening individual critical-analytical thinking abilities through education at school. It is hoped that individuals who have been coached, trained, and accustomed to being tolerant and caring at school can become citizens of society 5.0 who are wise in using social media. In this way, it is hoped that a high level of tolerant and socially caring character will be realized so that the ideals of a prosperous, civilized, and progressive society 5.0 will become a reality.